ANALISIS PERFORMA KONDENSOR DI PT. INDONESIA POWER UJP PLTU LONTAR BANTEN UNIT 2 - Redaksi Tim Jurnal (JURNAL POWERPLANT, 2017)
Steam Power Plant Lontar Bantam is built on an area of 94 hectares with a capacity of three generating units where each unit is 315 MW, bringing the total power capacity of 945 MW of electricity generated. The electric power generated Lontar Steam Power will be channeled through the 150 kV transmission lines along the 22 kilometers to the substation Teluk Naga and along the 22 kilometers to the new substation Tangerang. Working from the condenser has an influence on the performance rankine cycle. Condenser otherwise good performance when the heat transfer process that occurs in the condenser is progressing well. Heat transfer process is influenced by several things such as cleanliness tube, the amount of refrigerant flowing water, cooling water inlet temperature. The performance of the condenser is calculated at the time before overhaul and after overhaul. Condition after overhaul should be better than before the overhaul, if there is a decrease in performance then you can add what steps can be done to overcome it. In this study to calculate the performance of the condenser using a standard ASME PTC 12.2 – 2010 (Revision Of PTC 12.2–1998 (R2007) Steam Surface Condensers and in research condenser performance results after the overhaul is better than the performance of the condenser before overhaul.